Citra Perempuan Dalam Cerita Rakyat Timun Mas Dan Kaguyahime No Monogatari: Kajian Sastra Bandingan - Ryan Firmansyah; Bastian Zulyeno (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
Comparative literature is one of the theoretical approaches used to compare literary works, including folklore, which is an important part of oral tradition. Folktales, which are passed down from generation to generation, are interesting objects of study to analyze. This research aims to compare various aspects of feminism contained in the stories of Timun Mas and Kaguyahime No Monogatari. In analyzing these two stories, this research uses a comparative approach developed by Wellek & Warren and Ruthven's feminist approach. The method used is descriptive qualitative method with comparative literature study technique, which allows a detailed description of the similarities and differences between the two stories. The object of study in this research are the two folktales. The results of the analysis show that there are similarities between the two, which can be seen in the two main female characters who are trapped by the patriarchal culture carried out by male characters. However, the differences between the two can be seen in the reactions of the female protagonists when confronted with the patriarchal culture. This difference reflects two very different responses to social and gender norms in two different cultures, and shows how the role of women in a patriarchal society can be contrasted in literary works from different traditions.